Congenital left ventricular diverticulum repair in an adult with dual patch technique. Issue 7 (6th July 2020) - Mejia, Javier; Spindel, Stephen M.; Pawale, Amit; Itagaki, Shinobu; Boateng, Percy
Abstract: Rupture of a congenital left ventricular diverticulum (CLVD), a rare anatomical anomaly, is a catastrophic event, with potential fatal consequences. Repair techniques documented in the literature include primary closure and single patch closure. We describe a case of a 57‐year‐old woman with symptomatic anterolateral CLVD. Our approach involves a linear incision through the epicardial surface of the diverticulum with exclusion of the cavity, and restoration of normal ventricular geometry via a two‐patch technique.